Metastatic Renal Cell Carcinoma versus Pancreatic Neuroendocrine Tumor in von Hippel-Lindau Disease: Treatment with Interleukin-2 - Christopher Williams; McClellan Walther (The Scientific World Journal)
Differentiating between clear cell neuroendocrine tumor (NET) of the pancreas and renal cell carcinoma (RCC) metastatic to the pancreas can be challenging in patients with von Hippel-Lindau disease (VHL). The clear cell features of both NET and RCC in VHL patients may lead to misdiagnosis, inaccurate staging, and alternative treatment. We present a patient in which this occurred. As clear cell NETs closely resembling metastatic RCC are distinctive neoplasms of VHL and metastatic RCC to the pancreas in the VHL population is rare, careful pathologic examination should be performed prior to subjecting patients to definitive surgical or medical therapies.